The potential of miRNA-based approaches in glioblastoma: An update in current advances and future perspectives - Edgar G. Ordóñez-Rubiano, MD, PhD (c); Nicolás Rincón-Arias, MD; Sebastian Espinosa, MD; William J. Shelton, MD; Andres F. Salazar; Alba Cómbita, MSc, PhD; Matías Baldoncini, MD; Sabino Luzzi, MD, PhD; César Payán-Gómez, MD, PhD; Diego F. Gómez- Amarillo, MD, MSc; Fernando Hakim, MD; Javier G. Patiño-Gómez, MD; et al. (Current Research in Pharmacology and Drug Discovery)
Glioblastoma (GBM) is the most common malignant central nervous system tumor. The emerging field of epigenetics stands out as particularly promising. Notably, the discovery of micro RNAs (miRNAs) has paved the way for advancements in diagnosing, treating, and prognosticating patients with brain tumors. We aim to provide an overview of the emergence of miRNAs in GBM and their potential role in the multifaceted management of this disease. We discuss the current state of the art regarding miRNAs and GBM. We performed a narrative review using the MEDLINE/PUBMED database to retrieve peer-reviewed articles related to the use of miRNA approaches for the treatment of GBMs. MiRNAs are intrinsic non-coding RNA molecules that regulate gene expression mainly through post-transcriptional mechanisms. The deregulation of some of these molecules is related to the pathogenesis of GBM. The inclusion of molecular characterization for the diagnosis of brain tumors and the advent of less-invasive diagnostic methods such as liquid biopsies, highlights the potential of these molecules as biomarkers for guiding the management of brain tumors such as GBM. Importantly, there is a need for more studies to better examine the application of these novel molecules. The constantly changing characterization and approach to the diagnosis and management of brain tumors broaden the possibilities for the molecular inclusion of novel epigenetic molecules, such as miRNAs, for a better understanding of this disease.